Ireland’s 2010 EU/IMF intervention: Costs and benefits - van Bekkum, Sjoerd (Journal of Banking & Finance, 2016)
This paper examines the costs and benefits of the EU/IMF rescue package for Ireland, on November 29, 2010. We analyze the costs of the intervention and the subsequent increase in value of debt and/or equity issued by Irish banks, the Irish government, and European banks with substantial holdings of Irish debt. The total initial value increase around the announcement amounts to €5.59bln at a realized taxpayers’ cost of €4.23bln. While the value increase depends on somewhat generous assumptions, it further increases by €2.8bln up to Ireland’s exit in December 2013. About €3.1bln of the value created indirectly supports the European banking sector, indicating that substantial benefits arise from systemic risk containment.